Market Segmentation in Industrial Product-Service Companies: a Case Study - Nurminen, Elina (My University, 2018)
The topic of market segmentation is widely accepted among the industrial markets but it is often overlooked since the market structure is more complex and therefore segmentation can be problematic. The recent economic volatility and recession has had a major impact concerning project and product investments from the customer side, which has forced industrial companies to find ways to generate stable revenues and profits some other than traditional way. Therefore, product-service companies within industrial markets have become more common. The motivation for this thesis research and the main objective is to develop a segmentation approach for market segmentation in industrial product-service companies. The literature review of the thesis provides an overview of industrial market segmentation and servitization to identify the existing contributions within the topic. The review finds that segmentation in product-service companies requires the understanding of differing customer needs and value. Accordingly, a three-step theoretical segmentation approach is drafted to answer this need. The empirical study of this research is a single case study and uses workshops as the data collection method, aiming to further develop the theoretical segmentation approach for industrial market segmentation in product-service companies. The findings of the study suggest that the approach for segmentation in industrial product-service companies can be adjusted from a three-step approach to a six-step approach. It is identified, that the criteria used in the segmentation framework of the approach should be objective rather than subjective. Therefore, the research finds that a systematic process to do segmentation and an appropriate customer scope lead to a favorable result, which is segment homogeneity in a heterogenic market.
Keywords: market segmentation; industrial markets; servitization; product-service companies; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|